Efficacy and Safety in Retinal Vein Occlusion Treated with at Least Three Consecutive Intravitreal Dexamethasone Implants - Julia Proença Pina; Khalil Turki; Julien Labreuche; Alain Duhamel; Thi Ha Chau Tran (Journal of Ophthalmology)
Purpose. To evaluate the effects of repeated intravitreal dexamethasone implant (DI) (Ozurdex®) in eyes with macular edema (ME) due to retinal vein occlusion (RVO). Methods. Multicenter observational study including patients who received more than three consecutive DI on an “as-needed” basis for the treatment of ME in RVO. Results. A total of 18 eyes were included for analysis. Mean interval of retreatment with DI was 5.1 months between the first and second DI and 5.4 months following the second DI. Baseline BCVA was 0.74 ± 0.08 log-Mar; it significantly improved to 0.45 ± 0.04 2 months after the 3rd DI. There was no significant difference between the 3 first postinjection BCVA. CMT decreased from 617 μm ± 120 μm (baseline) to 330 ± 109 μm two months after the third DI. Elevated intraocular pressure occurred in 50% and was controlled medically. Cataract progression leading to cataract surgery occurred in 69% of phakic eyes after a mean interval of 17 months. Conclusion. Repeated DI on an “as-needed” basis, with a retreatment interval <6 months, are effective in the long term in the management of ME due to RVO. Rates of increased intraocular pressure and cataract surgery seem to be higher than previously described when eyes were followed during a longer period.